Faktor yang Mempengaruhi Nilai Perusahaan Sektor Barang Konsumsi yang Terdaftar di BEI - Wahyuni, Rici Sri; Banjarnahor, Haposan (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The value of a company is influenced by the growth (up / down) of the company. The purpose of this study is to impact profitability (ROA), leverage (DER), business growth (GROWTH), organizational ownership (AI), and management ownership (KM) on corporate value (PBV). It is to analyze at the same time. The subject of this survey consists of companies in the consumer goods subsector listed on the Indonesia Stock Exchange between 2018 and 2020. The sample selection process used a targeted sampling method to obtain samples from 43 of the 56 companies. This survey uses secondary data in the form of an annual report of consumer products companies. The data analysis method used multiple linear regression analysis. Profitability (ROA) has a significant negative impact on corporate value, leverage (DER) does not have a significant impact on corporate value, and corporate growth (GROWTH) is important. Positive effect on the value of the company, Institutional Ownership (AI) has a significant negative impact on corporate value, Management Ownership (KM) has a negative impact on corporate value, while at the same time profitability (ROA), leverage (DER), business growth (GROWTH), and institutional Ownership (KI) and managed assets (KM) have a significant impact on goodwill (PBV).Â